2000
DOI: 10.1016/s0008-6363(00)00182-6
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of the L-type calcium current in rabbit sino-atrial cells: effect on cardiac automaticity

Abstract: Facilitation of I(Ca,L) is present in rabbit sino-atrial cells. The underlying mechanism reflects modulation of I(Ca,L) decay kinetics by diastolic membrane potential and frequency of depolarization. This phenomenon may provide an important regulatory mechanism of sino-atrial automaticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Both I Na and I CaT have low voltage activation thresholds and, therefore, strongly amplified the initial cAMP-sensitive signaling of I f -induced early depolarization in the 1999 Demir et al model (6). However, I CaT was later found to be relatively small and detected only in 20% of rabbit SANCs (38); I Na is negligible in primary/central rabbit SANCs (initiating excitations in the sinoatrial node). Furthermore, being cAMP/PKA independent, I CaT cannot control late DD and the pacemaker rate.…”
Section: Comparisons With Other Sanc Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Both I Na and I CaT have low voltage activation thresholds and, therefore, strongly amplified the initial cAMP-sensitive signaling of I f -induced early depolarization in the 1999 Demir et al model (6). However, I CaT was later found to be relatively small and detected only in 20% of rabbit SANCs (38); I Na is negligible in primary/central rabbit SANCs (initiating excitations in the sinoatrial node). Furthermore, being cAMP/PKA independent, I CaT cannot control late DD and the pacemaker rate.…”
Section: Comparisons With Other Sanc Modelsmentioning
confidence: 98%
“…A critical parameter determining the ICaL contribution to DD is its activation threshold, and, therefore, this parameter was carefully considered in our model. The activation threshold has been measured in several patch-clamp studies of isolated rabbit SANCs and was found to be "positive to Ϫ45 to Ϫ50 mV" (8), "around Ϫ60 mV" (48), "between Ϫ50 and Ϫ40 mV" (38), or "approximately Ϫ40 mV" (52). A relatively low activation threshold of I CaL in SANCs might be explained, at least in part, by two factors: 1) L-type Ca 2ϩ channels could be phosphorylated by PKA, which is highly active in the basal state (43,50); and 2) ICaL in SANCs might be a combination of Cav1.2 and Cav1.3, as shown in mouse SANCs (37).…”
Section: Simulation Of I Cal In the Basal Statementioning
confidence: 99%
“…The inactivation of ICa,L consists of two exponential terms: rapid and slow components. The rapid component is mediated by the intracellular Ca 2ϩ -dependent inactivation with a time constant ranging from 10 to 30 ms for rabbit SA node cells, whereas the slower component reflects the voltage-dependent inactivation with a time constant of 30ϳ70 ms (5,34,72,81,102). To describe the inactivation process, we adopted a simple model in which the Ca 2ϩ -dependent inactivation process is independent of the voltage-dependent one (see Refs.…”
Section: Model Developmentmentioning
confidence: 99%
“…Modest depolarization induces an increase in I Ca amplitude and a slowing of I Ca inactivation, which was blocked by ryanodine, suggesting a role for sarcoplasmic reticulum Ca release (Barrere-Lemaire et al, Brette et al, 2003a). The mechanism and physiological role of this facilitation is not elucidated yet, although it has been suggested that it can regulate cardiac automaticity in sinoatrial node cells (Mangoni et al, 2000).…”
Section: Facilitationmentioning
confidence: 99%